2020
DOI: 10.1093/oso/9780197507445.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Strange Case of Donald J. Trump

Abstract: The Strange Case of Donald J. Trump provides a coherent and nuanced psychological portrait of the 45th president of the United States. Drawing on biographical events in Trump’s life and on contemporary research and theory in personality, social, and developmental psychology, the book explores the personality traits and psychological dynamics that have shaped Trump’s life, with an emphasis on the strangeness of the case—how Trump again and again defies psychological expectations regarding what it means to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…As perhaps the best symptomatic example, our data reveal that Trump's personality is characterised by extreme extraversion, off-the-charts narcissism, high psychopathy and Machiavellianism, very low agreeableness and low emotional stabilityall of which is in line with several accounts published elsewhere (e.g. Hamblin 2016;McAdams 2016McAdams , 2016Nai and Maier 2018;Nai et al 2019;Olbermann 2016;Visser et al 2017).…”
Section: Covariatessupporting
confidence: 91%
“…As perhaps the best symptomatic example, our data reveal that Trump's personality is characterised by extreme extraversion, off-the-charts narcissism, high psychopathy and Machiavellianism, very low agreeableness and low emotional stabilityall of which is in line with several accounts published elsewhere (e.g. Hamblin 2016;McAdams 2016McAdams , 2016Nai and Maier 2018;Nai et al 2019;Olbermann 2016;Visser et al 2017).…”
Section: Covariatessupporting
confidence: 91%
“…Regardless of their diagnostic value, these considerations overlapped with a narrative that portrays Donald J. Trump-the billionaire, the candidate, and now the president-as impetuous and quick to anger, thin skinned, constantly lying, insecure, brazen, vulgar, uninterested in details, and boasting a grandiose sense of self and an exaggerated vision of himself and his accomplishments (Cillizza 2018). Many have suggested that Trump exhibits "sky-high extroversion combined with off-the-chart low agreeableness [… and] grandiose narcissism" (McAdams 2016) and that he could possibly "present a diagnosis of psychopathy" (Olbermann 2016). His actions display "a messiah complex, no conscience, and lacks complete empathy" (Hoise 2017).…”
mentioning
confidence: 99%
“…The first author recently completed an intensive psychological study of the life and personality of U. S. President Donald J. Trump (McAdams, 2020). The study's central thesis is that Donald Trump has no inner story in his mind about who he is, how he came to be, and where his life may be going.…”
Section: Hexaco and The Individual Casementioning
confidence: 99%